The influence of pollution accumulation on coating aging of UHV line insulators with different suspension height in coal-ash polluted area - Lei Lan; Lin Mu; Yu Wang; Xiaoqing Yuan; Wei Wang; Zhenghui Li (Archives of Electrical Engineering, 2020)
Room temperature vulcanized (RTV) silicone rubber is widely used to prevent pollution flashover with its excellent hydrophobicity and hydrophobicity transfer. However, RTV coatings are at the risk of deterioration and failure in heavily polluted operating environment. In this paper, RTV coated insulators with different suspension heights operating in coal ash polluted areaswere sampled. Pollution degree, pollution composition and aging degree of coatings were tested. The result shows that the insoluble pollution contains Al(OH)3 filler precipitated from RTV coating, which indicates the aging of the RTV coating. The top surface coating is more affected by ultraviolet and rainwater than the bottom surface resulting in more serious degradation. As the pollution degree of the lower phase insulator is heavier than that of the upper phase insulator, the erosion effect of pollution on the RTV coating is more intense. The fillers and rubber molecules of RTV continuously precipitate into the pollution layer, leading to further aging. Therefore, the overall aging degree of the lower insulator coating is more serious than that of the upper insulator coating.